Role of Cognitive Appraisal in Coping, Adapting and Psychological Well-Being of Chinese Teachers: A Concept Paper - Xiaoli, Zhao; Veloo, Arsaythamby (South Asian Journal of Social Sciences and Humanities, 2024)
Teachers are considered a nucleus of educational institutes, their dire efforts act as the accelerating engine of the students’ minds that nurture their minds with the best, most incumbent, authentic, resilient and creative thoughts, knowledge, reasoning and information that play a back-supporting role to the future emperors of the countries in their professional life. To do such a huge and exhaustive job, teachers often encounter various challenging situations and circumstances in which stress can be placed at the top among all other issues. This delicate issue has been identified as common among Chinese university lecturers and this issue has been influencing their mental states causing a damaging effect on their job performance. To understand this deliberate scenario, this study has reviewed the previous literature to explore the level of stress and psychological well-being and some helping strategies to sustain psychological well-being and stress adaptation as it is a part of every job and propose a conceptual framework. This proposed framework will have many useful settings for the literature scholars and the targeted units which have been illustrated in the concluding remarks section.